2009
DOI: 10.1161/circresaha.108.190041
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Contributes to Gender Differences in Mouse Ventricular Repolarization

Abstract: Rationale Fast-transient outward K+ (Ito,f) and ultra-rapid delayed rectifier K+ currents (IKur or IK,slow) contribute to mouse cardiac repolarization. Gender studies on these currents have reported conflicting results. Objective One key missing piece information in these studies is the animals’ estral stage. We decided to revisit gender-related differences in K+ currents, taking into consideration the females’ estral stage. Methods and Results We hypothesized that changes in estrogen levels during the est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 30 publications
6
83
2
Order By: Relevance
“…Endogenous testosterone and progesterone shorten the action potential, 8,9,11 and estrogen lengthens the QTc interval in animals. 10 These effects occur through alterations in myocardial I Ca,L , I Kr , I Ks and I K1 channels, which control phases 2 and 3 of the cardiac action potential. Exogenous ET lengthens the QTc interval, and EPT has no effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endogenous testosterone and progesterone shorten the action potential, 8,9,11 and estrogen lengthens the QTc interval in animals. 10 These effects occur through alterations in myocardial I Ca,L , I Kr , I Ks and I K1 channels, which control phases 2 and 3 of the cardiac action potential. Exogenous ET lengthens the QTc interval, and EPT has no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Saito et al 10 compared the QTc of mice with high endogenous estrogen to the QTc of ovariectomized mice with no detectable endogenous estrogen. They found a significantly shorter QTc in the ovariectomized group ( p < 0.05).…”
Section: Endogenous Sex Hormones and Qt Intervalmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the expression of NELL2 mRNA peaked at the proestrous phase, when circulating E2 concentrations are high- est (Saito et al, 2009). This finding is consistent with the results of our previous studies showing that E2 activates NELL2 transcription (Choi et al, 2010) and that NELL2 is expressed in the ERα expressing hypothalamic cells (Choi et al, 2010;Jeong et al, 2008a).…”
Section: Discussionmentioning
confidence: 77%
“…We observed similar additive beneficial effects of E2 and sildenafil treatments in male pressure-overload models (Supplemental Figure 8). Thus, the primary difference in sildenafil efficacy between OVX females and males derives from the drug's dependence on estrogen, as the estrogen levels themselves are comparable (25). We further examined this difference in isolated cardiomyocytes in acute settings.…”
Section: Gender Differences In Sildenafil Responses and The Mechanismmentioning
confidence: 99%